GAMBARAN KONFLIK BERMATRAS AGAMA DI INDONESIA (PROBLEM SOLVING BERBASIS TEOLOGI TRANSFORMATIF) - Rizal, Toha Rudin (State Institute for Islamic Studies Batusangkar, 2016)
The religious conflicts in Indonesia were inter-religious conflicts, conflict between the religious groups as heretical, and the internal conflicts of the religion-people who have a different understanding. This article examines the intensely about the issue and attempt to uncover the root of problems behind. From this analysis, there was significance paradigmatic model of resolution based holistic theology and transformative. Theology transformative demands the people to escape from the burdens of religious history that often distorts the religion intrinsic value and its role. Through the development of this theology, human will be seen as the creative process and the full responsibility for developing life in the values of morality perennial, justice, peace and prosperity.Keywords: Religious Conflict, Theology Transformative, Indonesia.